(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Protein aggregation is the process by which misfolded proteins self-assemble into soluble oligomers and insoluble aggregates. An isocratic HP-SEC method was developed in order to determine the protein aggregation in the Calcitonin Salmon injection. Since the label claim of the Calcitonin Salmon in Calcitonin Salmon is 33.33mg/ml at this level of test concentration, no aggregate was observed even with 500 ml injection volume of as such test preparation. Therefore, to detect aggregates or high molecular weight impurities, attempts were made to increase the test concentration of Calcitonin Salmon injection by evaporating the test product under a nitrogen stream and subsequently reconstituting it with a diluent. An isocratic HP-SEC method was developed in order to determine the protein aggregation in the Calcitonin Salmon injection. The chromatographic separation was achieved at SEC column i.e., Insulin, HMWP, 300 x 7.8 mm with 0.1%TFA in mixture of Water: Acetonitrile (70:30) with the flow rate 0.5 ml/min. 100 µl of samples were injected at 40°C column temperature and UV detection occurred at 220 nm. The developed method is highly specific and oligomers are completely separated from the principal peak with USP resolution of 1.5. The developed method was found to be accurate, linear, and precise in the range of 0.092 μg/ml to 300 μg/ml. The method also examined with stress factors such as temperature, light, agitation, freezing, and thawing to identify and study the factors that induces the aggregation of Calcitonin Salmon in Calcitonin Salmon drug product.